Diagnostic promiscuity: the use of real-world data to study multimorbidity in mental health. (May 2021) - Arias de la Torre, Jorge; Ronaldson, Amy; Valderas, Jose M.; Vilagut, Gemma; Serrano-Blanco, Antoni; Hatch, Stephani L.; Alonso, Jordi; Hotopf, Matthew; Dregan, Alexandru
Abstract : Mental health-related multimorbidity can be considered as multimorbidity in the presence of a mental disorder. Some knowledge gaps on the study of mental health-related multimorbidity were identified. These knowledge gaps could be potentially addressed with real-world data.